Introduction - Franke, Katherine (Columbia Journal of Gender and Law, 2011)
Each year Columbia Law School’s Center for Gender Sexuality Law selects a scholar whose work has made an important impact on the study and practice of gender and/or sexuality law. For 2010 we selected Judith Butler, the Maxine Elliot Professor in the Departments of Rhetoric and Comparative Literature at the University of California, Berkeley. In March of 2010, we held a Symposium recognizing the multiple domains of theory and activism in which Butler’s mark has been profound, and oft times paradigm shifting. Columbia Law School has the great fortune of having developed one of the deepest and most diverse faculties engaged in the study of the law of gender and sexuality. In turn, this has drawn a most magnificent body of students to our law school, many of who were involved in making this Symposium a success. I want to acknowledge and thank them for their hard work. Our students, no less than those of us who work in the academy, are the beneficiaries over and again of the creativity and sheer courage of Butler’s ideas.